The Need for a Socio-Geographical Approach to the Study of Ethnoecological Culture - Komilova Nargiza Urinovna (Zien Journals, 2022)
Since the purpose of this study is to study the geographical aspects of ethno-ecological culture, a systematic approach is necessary here, which provides the opportunity to study natural and social directions at the same time. The reason is that social, economic, natural and ecological indicators and their interrelationship are taken as elements of ethno-ecological culture.
Keywords: Ethno-ecological culture; natural-ecological character; historical approach; historical ethnographic regions